Evaluation of the Relationships Between Burnout, Eating Behavior and Quality of Life in Academics : Burnout, Eating Behaviour and Quality of Life - ATEŞ ÖZCAN, BURCU; Uslu, Burcu; Okudan, Begüm; Alphan, Müveddet Emel (Progress in Nutrition, 2021)
Background: Burnout may lead to decreased healthy eating behaviors. Particularly intense and strenuous working conditions in academicians can increase burnout and decrease quality of life by negatively affecting health. Objectives: The study was conducted to examine the burnout level, eating behaviors and quality of life of academicians and to reveal the relationship between these parameters. Methods: 194 academicians who accepted to participate voluntarily in the study were included. A questionnaire form about the socio-demographic characteristics, Dutch Eating Behaviors Questionnaire (DEBQ), Maslach Burnout Inventory- Educator Survey and Quality of Life Questionnaire -Short Form (SF-36) were applied to the participants. Results: Emotional eating score has positive relationships with emotional burnout and depersonalization, and has a negative relationship with personal success (p≥0.05). Emotional eating score has positive meaningless relationships with physical function and social functionality which are sub parameters of quality of life. While positive relationships between personal success and all parameters other than pain from the quality of life sub parameters are observed. Conclusions: Emotional eating and burnout can have negative effects on academicians' quality of life. Taking precautions to increase healthy nutrition and physical activity in academic staff and being directed by experts in their field can be effective in preventing this problem.